Strength and conditioning practices in adolescent rugby players: Relationship with changes in physical qualities - Weakley, J. J. S.; Till, K.; Darrall-Jones, J.; Roe, G. A. B.; Phibbs, P. J.; Read, D. B.; Jones, B. L. (The Journal of Strength and Conditioning Research, 2019)
Adolescent rugby players benefit from the implementation of resistance training. However resistance training practices and how they influence short-term physical change is unknown. Therefore, the purpose of this study was to quantify resistance training practices, evaluate physical development, and relate these changes to resistance training variables across 12 weeks in adolescent rugby union players. Thirty-five male adolescent rugby union players participated in the study with subjects completing an anthropometric and physical testing battery before and after a 12-week in-season mesocycle. Subjects recorded resistance training frequency, exercises, repetitions, load, minutes, and rating of perceived exertion for each session using weekly training diaries during the 12-week period. Paired sample t tests and Cohen's d effect sizes were used to assess change, whereas Pearson correlation coefficients assessed relationships between variables. Resistance training practices were variable, although significant (p = 0.05) improvements in body mass, countermovement jump (CMJ) height, front squat, bench press, and chin-up strength were observed. Resistance training volume load had moderate to strong relationships with changes in CMJ (r = 0.71), chin up (r = 0.73), and bench press (r = 0.45). Frequency of upper and lower-body compound exercises had significant moderate to large relationships with changes in CMJ (r = 0.68), chin up (r = 0.65), and bench press (r = 0.41). Across a 12-week in-season period, adolescent rugby union players have varying resistance training practices, although anthropometric and physical characteristics seem to improve. Given the observed relationships, increased volume loads through the implementation of free-weight compound exercises could be an effective method for improving physical qualities in young rugby players.